Woman and pregnancy: focus on depression and psychopharmacological therapy - Cristina, Davide (International Journal of Basic & Clinical Pharmacology, 2023)
Perinatal depression is one of the most common complications of pregnancy: it affects about 10-15% of women; the object of clinical attentionis postpartum depression (PPD) because it involves a impairment of the social and personal functioning of affected women and can have repercussions on the partner on the quality of life, on mother-infant interaction and neurodevelopment of the product of conception. Selective serotonin reuptake inhibitors (SSRI) are generally consideredas first-line antidepressant treatment in pregnancy, as they are generally safe and effective. Studies concerning the adverse effects of exposure to SSRIs during pregnancy on the developing foetushaveindicated an increased risk of various congenital malformations and un toward effects such as poor neonatal adaptation syndrome or persistent pulmonary hypertension, but here still remain inconsistencies between various study results. PPD can be a preventable disorder, there fore it be comes important that integrated actions between different medical sectors (interdisciplinary), diagnosis and any interventions are effective.